2015
DOI: 10.1007/s00223-015-0081-7
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive Assessment of Lower Limb Geometry and Strength Using Hip Structural Analysis and Peripheral Quantitative Computed Tomography: A Population-Based Comparison

Abstract: Hip fracture is the most significant complication of osteoporosis in terms of mortality, long-term disability and decreased quality of life. In the recent years, different techniques have been developed to assess lower limb strength and ultimately fracture risk. Here we examine relationships between two measures of lower limb bone geometry and strength; proximal femoral geometry and tibial peripheral quantitative computed tomography. We studied a sample of 431 women and 488 men aged in the range 59–71 years. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Independent of BMD, bone geometry contributes to fracture risk [ 6 , 7 , 8 ]. Geometric parameters of the femoral neck, such as cross-sectional area (CSA), buckling ratio (BR), and section modulus (SM) [ 9 ] also describe bone strength and are independently predictive of hip fragility fracture [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Independent of BMD, bone geometry contributes to fracture risk [ 6 , 7 , 8 ]. Geometric parameters of the femoral neck, such as cross-sectional area (CSA), buckling ratio (BR), and section modulus (SM) [ 9 ] also describe bone strength and are independently predictive of hip fragility fracture [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of sex differences in bone geometry across adult lifespan have consistently demonstrated that compared to women, men have greater aerial BMD, cross-sectional bone areas (CSA), bone diameters, section moduli (bending strength; SM), and lower buckling ratio (cortical instability; BR) at the narrow neck (NN), intertrochanteric region (IT), and femoral shaft (FS) [1,5,1116]. Cross-sectional investigations indicate that BMD decreases with age in both men and women but expansions in outer diameter serve to preserve bending strength and compensate for net BMD decline [1,12,15,17].…”
Section: 0 Introductionmentioning
confidence: 99%